2020
DOI: 10.1111/os.12710
|View full text |Cite
|
Sign up to set email alerts
|

Cup‐Cage Solution for Massive Acetabular Defects: A Systematic Review and Meta‐Analysis

Abstract: Our systematic review compiled multiple studies and evaluated survivorship and clinical outcomes of cup‐cage construct usage in the management of massive acetabular bone defects. This systematic review was conducted according to the Preferred Reporting Items for Systematic Reviews and Meta‐Analyses (PRISMA) guidelines. Various combinations of “acetabular”, “pelvis”, “cup cage” and their corresponding synonyms were used to search relevant articles in the Cochrane, EMBASE, and PubMed databases. Basic information… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 33 publications
1
16
0
Order By: Relevance
“…The main reason for revision was dislocation (6.4% of cases), infection (6.4% of cases) and aseptic loosening (3.5% of cases). Similar results were presented in a more recent systematic review by Wang et al, 63 who reported the outcome of 232 patients who underwent revision THR, mainly presenting with AAOS type III and type IV defects. The mean follow-up period was 48.85 months (range, 1–140).…”
Section: Cages and Ringssupporting
confidence: 87%
“…The main reason for revision was dislocation (6.4% of cases), infection (6.4% of cases) and aseptic loosening (3.5% of cases). Similar results were presented in a more recent systematic review by Wang et al, 63 who reported the outcome of 232 patients who underwent revision THR, mainly presenting with AAOS type III and type IV defects. The mean follow-up period was 48.85 months (range, 1–140).…”
Section: Cages and Ringssupporting
confidence: 87%
“…A systematic review and meta-analysis, which included a study of the results of using cup-cage constructs in 232 cases of revision arthroplasty, showed the proportion of revisions of the acetabular component was 8% (12 cases). In 8 of these 12 cases, the reason for revision was aseptic loosening; the average follow-up was 48.8 months [28].…”
Section: Discussionmentioning
confidence: 99%
“…A polyethylene liner is then cemented in the cage in the correct position. Advantages of this technique are its favourable outcomes and high survival rates, ranging from 75–100% [ 37 , 42 , 48 , 49 , 50 , 51 , 52 ]. The main complications of this technique are dislocation (7–8%), infection (4–7%) and aseptic loosening (4–15%) [ 37 , 42 , 48 , 49 ].…”
Section: Treatmentmentioning
confidence: 99%
“…Advantages of this technique are its favourable outcomes and high survival rates, ranging from 75–100% [ 37 , 42 , 48 , 49 , 50 , 51 , 52 ]. The main complications of this technique are dislocation (7–8%), infection (4–7%) and aseptic loosening (4–15%) [ 37 , 42 , 48 , 49 ]. Acetabular distraction was first described by Sporer et al in 2012 [ 53 ].…”
Section: Treatmentmentioning
confidence: 99%